A nanolayered MXene ion crosslinking composite electrode, a flexible driving device and a preparation method thereof

CN123017854APending Publication Date: 2026-10-30YANAN UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611269368.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但简单物理混合无法使聚吡咯有效进入纳米级层间空间,层间距离撑开效果有限

Benefits of technology

[0016]本发明的有益效果为:本发明通过原位聚合和金属离子配位交联的协同作用,在MXene纳米片层间构建物理撑开与化学锁定双重限域网络,使层间距离显著增大且保持结构稳定,循环寿命大幅延长,同时聚吡咯在MXene层间的原位填充以及金属离子交联剂的配位锚定,构建了兼具高电子导电性和高离子通透性的三维复合网络,电极比电容显著提升。其次本发明柔性驱动器件通过错位区域的结构设计实现非对称电化学应变,在低频驱动条件下尖端位移幅值大幅提升,同时具备良好的高频响应特性,兼顾低频大位移驱动能力和中高频响应能力,且采用一锅法串联工艺,在MXene分散液中依次完成原位聚合和金属离子交联,无需中间分离纯化步骤,制备工艺简练高效,电极结构均一性优良,适合批量化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017854A_ABST
    Figure CN123017854A_ABST
Patent Text Reader

Abstract

The application discloses a nano-layered MXene ion cross-linking composite electrode, a flexible driving device and a preparation method thereof, relates to the technical field of nanocomposites and flexible driving devices, and the composite electrode comprises Ti3C2T x MXene nanosheets, polypyrrole and a metal ion cross-linking agent, multilayer Ti3C2T x MXene nanosheets are stacked to form a layered skeleton structure, polypyrrole is filled in the interlayer space of the MXene nanosheets in situ, and the metal ion cross-linking agent forms a coordination bond with oxygen-containing functional groups on the surface of the MXene nanosheets; the flexible driving device comprises a first electrode layer, an electrolyte layer and a second electrode layer which are sequentially stacked, and the first electrode layer and the second electrode layer form a misregistration area in the length direction; the application constructs a double-limited network through the synergistic effect of in-situ polymerization and metal ion cross-linking, significantly increases the interlayer distance and inhibits the slip of the sheet layer, and greatly improves the specific capacitance of the electrode and the driving deformation capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanocomposite materials and flexible actuators, and particularly to a nanolayered MXene ion-crosslinked composite electrode, a flexible actuator, and a method for preparing the same. Background Technology

[0002] Ion-driven electroactive polymer actuators possess advantages such as low driving voltage, large deformation, and high energy density, and have broad application prospects in flexible robotics, artificial muscles, and microfluidic control. Electrode materials are the core components determining the performance of ion actuators, requiring high electronic conductivity, excellent flexibility, and good cycling stability.

[0003] MXene is a novel two-dimensional transition metal carbonitride (of which Ti3C2T) x As a typical example, Ti represents titanium, C represents carbon, T represents surface terminal functional groups, and x represents the number of functional groups. It possesses both metallic conductivity and a hydrophilic surface, making it an ideal candidate material for ion-driven electrodes. However, Ti3C2T... x The strong van der Waals forces between MXene nanosheets lead to their tight stacking, resulting in an interlayer distance of less than 1.1 nm. This makes it difficult for electrolyte ions to intercalate and deintercalate effectively, limiting the electrochemical activity and deformation-driving capability of the electrode. Furthermore, the insufficient mechanical flexibility of pure MXene films makes them prone to microcracks during repeated bending, leading to a significant decrease in cycle life.

[0004] To overcome the aforementioned shortcomings, researchers have attempted to composite conductive polymers with MXene to widen the interlayer distance. Polypyrrole (PPy) possesses high conductivity and good electrochemical activity, and is widely used in MXene composite modification. However, simple physical mixing cannot effectively allow polypyrrole to enter the nanoscale interlayer space, resulting in limited interlayer distance widening. Furthermore, polypyrrole undergoes significant volume expansion and contraction during charge-discharge cycling, causing the layered structure of the composite electrode to gradually collapse during cycling, leading to a rapid decrease in capacitance retention. Therefore, this invention proposes a nanolayered MXene ion-crosslinked composite electrode, a flexible actuator, and its preparation method to address the problems existing in the prior art. Summary of the Invention

[0005] To address the aforementioned problems, the present invention aims to propose a nanolayered MXene ion-crosslinked composite electrode, a flexible actuator, and its preparation method. The present invention utilizes the synergistic effect of in-situ polymerization and metal ion coordination crosslinking to construct a dual confinement network of physical expansion and chemical locking between MXene nanosheets, thereby achieving precise control of interlayer distance and long-term cyclic structural stability, thus solving the problems existing in the prior art.

[0006] To achieve the objectives of this invention, the invention is implemented through the following technical solution: a nanolayered MXene ion-crosslinked composite electrode, wherein the nanolayered MXene ion-crosslinked composite electrode comprises Ti3C2T x MXene nanosheets, polypyrrole, and metal ion crosslinking agents, in a multilayer structure of Ti3C2T x MXene nanosheets are stacked to form a layered framework structure, wherein adjacent Ti3C2T nanosheets are in the layered framework structure. x The interlayer spacing between MXene nanosheets is 1.2 nm to 1.8 nm, and the polypyrrole is in situ filled in the interlayer space of the MXene nanosheets. The metal ion crosslinking agent and Ti3C2T x The oxygen-containing functional groups on the surface of MXene nanosheets form coordination bonds, and the nanolayered MXene ion-crosslinked composite electrode has a thin film structure with an electrode thickness.

[0007] A further improvement is that the metal ion crosslinking agent is selected from Fe. 3+ Ca 2+ Or Al 3+ One of them, the Ti3C2T x The mass ratio of MXene nanosheets to polypyrrole is 1:0.2 to 1:1, and the electrode thickness is 5 μm to 50 μm.

[0008] Further improvements are made in that the specific capacitance of the nanolayered MXene ion-crosslinked composite electrode at a current density of 1 A / g is 380 F / g to 520 F / g, and the capacitance retention rate is 85% to 94% after 1000 bending cycles.

[0009] A flexible actuator constructed from a nanolayered MXene ion-crosslinked composite electrode is disclosed. The flexible actuator includes a first electrode layer, an electrolyte layer, and a second electrode layer stacked sequentially. Both the first and second electrode layers are nanolayered MXene ion-crosslinked composite electrodes. The electrolyte layer is a gel polymer electrolyte, which fills the space between the first and second electrode layers. Both the first and second electrode layers are rectangular sheet structures with sheet width and sheet length. The first electrode layer has a first electrode layer thickness, and the second electrode layer has a second electrode layer thickness. A misalignment region is formed at the second end of the first and second electrode layers in the length direction, and the misalignment region has a misalignment region length.

[0010] A further improvement is that the gel polymer electrolyte is composed of polyvinyl alcohol, deionized water and phosphoric acid, and the mass ratio of polyvinyl alcohol, deionized water and phosphoric acid is 1:8:1 to 1:12:1; the thickness of the gel polymer electrolyte is 20μm to 80μm.

[0011] Further improvements include: the sheet width is 2mm~10mm, the sheet length is 10mm~40mm, the ratio of the thickness of the first electrode layer to the thickness of the second electrode layer is 0.8:1~1.2:1, the first electrode layer and the second electrode layer are aligned at both ends in the width direction, the first electrode layer and the second electrode layer are flush at their first ends in the length direction, the misaligned area is 4mm~8mm long, and the misaligned area is used to connect to an external driving power supply.

[0012] A further improvement is that, under ±1.5V square wave voltage driving, the tip displacement amplitude of the flexible actuator is 8mm~15mm at a frequency of 0.1Hz, and the tip displacement amplitude can still maintain 20%~40% of the tip displacement amplitude at a frequency of 0.1Hz at a frequency of 10Hz.

[0013] A method for fabricating a flexible actuation device includes the following steps: Step 1: Add lithium fluoride to hydrochloric acid solution and stir until the lithium fluoride is completely dissolved to obtain an etching solution. Then, add Ti3AlC2MAX phase powder to the etching solution and stir the reaction at 35℃~45℃ for 24h~48h to obtain the reaction product. After that, wash the reaction product with deionized water until the pH value is 6~7, and then separate it by centrifugation to obtain Ti3C2T. x MXene precipitation, then Ti3C2T x MXene precipitate was dispersed in deionized water and subjected to ultrasonic exfoliation under inert gas protection and light-protected conditions for 1-3 hours. The supernatant dispersion was collected by centrifugation to obtain Ti3C2T. x MXene nanosheet dispersion; Step 2: To Ti3C2T x Pyrrole monomer was added to an MXene nanosheet dispersion and stirred at 0℃~5℃ for 30min~60min to obtain a mixed dispersion. An oxidant solution was then added dropwise to the mixed dispersion, and the reaction was carried out at 0℃~5℃ for 6h~12h to allow the pyrrole monomer to react in Ti3C2T. x MXene nanosheets are polymerized in situ to form polypyrrole, resulting in an MXene-polypyrrole composite dispersion. Step 3: Add a metal ion crosslinking agent solution to the MXene-polypyrrole composite dispersion and stir at room temperature for 2-4 hours to obtain a crosslinked composite dispersion; Step 4: The cross-linked composite dispersion is deposited on the surface of the filter membrane by vacuum filtration and dried under vacuum for 12h~24h. The dried composite film is then peeled off from the surface of the filter membrane to obtain a nano-layered MXene ion cross-linked composite electrode. The nano-layered MXene ion cross-linked composite electrode is then cut into a first electrode layer and a second electrode layer. Step 5: Mix polyvinyl alcohol, deionized water and phosphoric acid in a mass ratio of 1:8:1 to 1:12:1, and stir at 85℃ to 95℃ for 2 to 4 hours to obtain a gel polymer electrolyte. Then, coat the gel polymer electrolyte onto the surface of the first electrode layer, and cover the surface of the gel polymer electrolyte with the second electrode layer, so that the gel polymer electrolyte fills the space between the first electrode layer and the second electrode layer. Allow it to stand and cure at room temperature for 12 to 24 hours to obtain the flexible actuator.

[0014] A further improvement is made in the following: in step one, the concentration of the hydrochloric acid solution is 6 mol / L to 12 mol / L, the mass-to-volume ratio of the lithium fluoride to the hydrochloric acid solution is 1 g:10 mL to 1 g:20 mL, and the mass ratio of the Ti3AlC2MAX phase powder to the lithium fluoride is 1:1 to 1:2.

[0015] A further improvement is made in step two, where the pyrrole monomer reacts with the Ti3C2T... x The mass ratio of MXene nanosheets is 0.2:1 to 1:1; the oxidant solution is an aqueous solution of ammonium persulfate, and the concentration of the aqueous solution of ammonium persulfate is 0.1 mol / L to 0.5 mol / L; the molar ratio of ammonium persulfate to pyrrole monomer is 1:1 to 1.5:1.

[0016] The beneficial effects of this invention are as follows: This invention constructs a dual-confined network of physical expansion and chemical locking between MXene nanosheets through the synergistic effect of in-situ polymerization and metal ion coordination crosslinking. This significantly increases the interlayer distance while maintaining structural stability, resulting in a substantial extension of cycle life. Simultaneously, the in-situ filling of polypyrrole between MXene layers and the coordination anchoring of the metal ion crosslinking agent construct a three-dimensional composite network with both high electronic conductivity and high ion permeability, significantly improving the electrode specific capacitance. Secondly, the flexible actuation device of this invention achieves asymmetric electrochemical strain through the structural design of misaligned regions, significantly increasing the tip displacement amplitude under low-frequency driving conditions while possessing excellent high-frequency response characteristics. It balances low-frequency large displacement driving capability with mid-to-high-frequency response capability. Furthermore, it employs a one-pot series process, sequentially completing in-situ polymerization and metal ion crosslinking in the MXene dispersion, eliminating the need for intermediate separation and purification steps. The preparation process is simple and efficient, with excellent electrode structure uniformity, making it suitable for mass production. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of the electrode structure of the present invention.

[0018] Figure 2 This is a schematic diagram of the flexible drive device architecture of the present invention. Detailed Implementation

[0019] To enhance understanding of the present invention, the present invention will be further described in detail below with reference to embodiments. These embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.

[0020] In the following embodiments: X-ray diffraction testing used CuKα rays as the radiation source, with a scanning range of 2°~10° and a scanning speed of 0.5° / min. The interlayer distance was calculated based on the (002) diffraction peak position using the Bragg equation 2d·sinθ=nλ.

[0021] Electrochemical performance testing employed a three-electrode system, using a nanolayered MXene ion-crosslinked composite electrode as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel electrode as the reference electrode. The electrolyte was a 1 mol / L sodium sulfate aqueous solution. Cyclic voltammetry and constant current charge-discharge tests were performed on an electrochemical workstation. Specific capacitance was calculated based on the constant current charge-discharge curves.

[0022] The bending cycle test was conducted using a self-made bending fatigue testing machine. The electrode film was wound onto a cylindrical rod with a diameter of 5 mm and then released, which was counted as one bending cycle. The cycle frequency was 0.5 Hz. Samples were taken after every 200 cycles to test the electrochemical performance.

[0023] The tip displacement test uses a laser displacement sensor to measure the free end displacement amplitude of the flexible actuator when a ±1.5V square wave voltage is applied, with test frequencies of 0.1Hz and 10Hz. Example 1 according to Figures 1-2 As shown, this embodiment provides a nanolayered MXene ion-crosslinked composite electrode and its flexible actuation device, the preparation method of which is as follows: Step 1: Add 1g of lithium fluoride to 10mL of 6mol / L hydrochloric acid solution and stir until the lithium fluoride is completely dissolved to obtain an etching solution. Then, add 1g of Ti3AlC2MAX phase powder to the etching solution and stir the reaction at 35℃ for 24 hours to obtain the reaction product. Next, wash the reaction product with deionized water until the pH value is 6, and then separate it by centrifugation to obtain Ti3C2T. x MXene precipitation, then Ti3C2T x MXene precipitate was dispersed in deionized water and subjected to ultrasonic exfoliation under inert gas protection for 1 hour. The supernatant dispersion was collected by centrifugation to obtain Ti3C2T.x MXene nanosheet dispersion.

[0024] Step 2: To Ti3C2T x Pyrrole monomer was added to the MXene nanosheet dispersion, and the pyrrole monomer reacted with Ti3C2T x The mass ratio of MXene nanosheets was 0.2:1. The mixture was stirred at 0℃ for 30 minutes to obtain a mixed dispersion. Then, a 0.1 mol / L ammonium persulfate aqueous solution was added dropwise to this dispersion. The molar ratio of ammonium persulfate to pyrrole monomer was 1:1. The reaction was carried out at 0℃ for 6 hours to allow the pyrrole monomer to react in Ti3C2T. x MXene nanosheets are polymerized in situ to form polypyrrole, resulting in an MXene-polypyrrole composite dispersion. Step 3: Add a 0.05 mol / L FeCl3 (ferric chloride) aqueous solution to the MXene-polypyrrole composite dispersion. The volume ratio of FeCl3 aqueous solution to MXene-polypyrrole composite dispersion is 1:20. Stir at room temperature for 2 hours to obtain a cross-linked composite dispersion. Step 4: The cross-linked composite dispersion was deposited on the surface of a polyvinylidene fluoride filter membrane with a pore size of 0.22 μm by vacuum filtration. It was dried under vacuum at 40°C for 12 hours. The dried composite film was peeled off from the surface of the filter membrane to obtain a nano-layered MXene ion cross-linked composite electrode with a thickness of 5 μm. The nano-layered MXene ion cross-linked composite electrode was then cut into a first electrode layer and a second electrode layer. Step 5: Mix polyvinyl alcohol, deionized water, and phosphoric acid at a mass ratio of 1:8:1 and stir at 85°C for 2 hours to obtain a gel polymer electrolyte. Then, coat the gel polymer electrolyte onto the surface of the first electrode layer, and then cover the gel polymer electrolyte surface with the second electrode layer, creating a 4mm long misalignment region between the first and second electrode layers. This misalignment region is used to connect to an external driving power supply, while the gel polymer electrolyte fills the space between the first and second electrode layers, with a thickness of 20μm. Afterward, allow it to cure at room temperature for 12 hours to obtain a flexible actuator.

[0025] Furthermore, both the first and second electrode layers are rectangular sheet structures with a sheet width of 2 mm and a sheet length of 10 mm. The thickness ratio of the first electrode layer to the second electrode layer is 0.8:1. The first and second electrode layers are aligned at their ends in the width direction and flush at their first ends in the length direction.

[0026] X-ray diffraction was performed on the nanolayered MXene ion-crosslinked composite electrode obtained in this embodiment. The test conditions were: CuKα (copper target Kα) rays as the radiation source, and the scanning range was 2°~10°. The interlayer distance was calculated using the Bragg equation based on the (002) diffraction peak position. The calculated interlayer distance was 1.2 nm.

[0027] The electrochemical performance of the nanolayered MXene ion-crosslinked composite electrode obtained in this embodiment was tested, and the specific capacitance at a current density of 1 A / g was 380 F / g. After 1000 bending cycles, the capacitance retention was 85%.

[0028] The driving performance of the flexible actuator obtained in this embodiment was tested. Under ±1.5V square wave voltage driving, the tip displacement amplitude was 8mm at a frequency of 0.1Hz; the tip displacement amplitude could be maintained at 20% of the tip displacement amplitude at a frequency of 10Hz.

[0029] Example 2 according to Figures 1-2 As shown, this embodiment provides a nanolayered MXene ion-crosslinked composite electrode and its flexible actuation device, the preparation method of which is as follows: Step 1: Add 2g of lithium fluoride to 20mL of 12mol / L hydrochloric acid solution and stir until the lithium fluoride is completely dissolved to obtain an etching solution. Then, add 2g of Ti3AlC2MAX phase powder to the etching solution and stir the reaction at 45℃ for 48 hours to obtain the reaction product. Next, wash the reaction product with deionized water until the pH value is 7, and then separate it by centrifugation to obtain Ti3C2T. x MXene precipitation, then Ti3C2T x MXene precipitate was dispersed in deionized water and subjected to ultrasonic exfoliation under inert gas protection for 3 hours. The supernatant dispersion was collected by centrifugation to obtain Ti3C2T. x MXene nanosheet dispersion.

[0030] Step 2: Apply the above Ti3C2T x Pyrrole monomer was added to the MXene nanosheet dispersion, and the pyrrole monomer reacted with Ti3C2T x MXene nanosheets were mixed at a mass ratio of 1:1 and stirred at 5°C for 60 minutes to obtain a mixed dispersion. Then, a 0.5 mol / L ammonium persulfate aqueous solution was added dropwise to this dispersion. The molar ratio of ammonium persulfate to pyrrole monomer was 1.5:1. The reaction was carried out at 5°C for 12 hours to allow the pyrrole monomer to react in Ti3C2T. x MXene nanosheets are polymerized in situ between layers to form polypyrrole, thus obtaining an MXene-polypyrrole composite dispersion.

[0031] Step 3: Add a 0.2 mol / L FeCl3 aqueous solution to the MXene-polypyrrole composite dispersion. The volume ratio of the FeCl3 aqueous solution to the MXene-polypyrrole composite dispersion is 1:5. Stir at room temperature for 4 hours to obtain a cross-linked composite dispersion.

[0032] Step 4: The cross-linked composite dispersion was deposited on the surface of a polytetrafluoroethylene filter membrane with a pore size of 0.45 μm by vacuum filtration. It was dried under vacuum at 60°C for 24 hours. The dried composite film was peeled off from the surface of the filter membrane to obtain a nano-layered MXene ion cross-linked composite electrode with a thickness of 50 μm. The nano-layered MXene ion cross-linked composite electrode was then cut into a first electrode layer and a second electrode layer.

[0033] Step 5: Mix polyvinyl alcohol, deionized water, and phosphoric acid in a mass ratio of 1:12:1 and stir at 95°C for 4 hours to obtain a gel polymer electrolyte. Then, coat the gel polymer electrolyte onto the surface of the first electrode layer, and then cover the surface of the gel polymer electrolyte with the second electrode layer, so that the first electrode layer and the second electrode layer form a misaligned region in the length direction. The misaligned region is 8 mm long and is used to connect the external driving power supply. At the same time, the gel polymer electrolyte is filled between the first electrode layer and the second electrode layer, and the electrolyte layer thickness is 60 μm. Then, let it stand and cure at room temperature for 24 hours to obtain a flexible drive device.

[0034] Both the first and second electrode layers are rectangular sheet structures, with a sheet width of 10 mm and a sheet length of 40 mm. The thickness ratio of the first electrode layer to the second electrode layer is 1.2:1. The first and second electrode layers are aligned at their ends in the width direction and flush at their first ends in the length direction.

[0035] The nanolayered MXene ion-crosslinked composite electrode obtained in this embodiment was subjected to X-ray diffraction testing under the same conditions as in Example 1. The interlayer distance was calculated to be 1.8 nm.

[0036] The electrochemical performance of the nanolayered MXene ion-crosslinked composite electrode obtained in this embodiment was tested, and the specific capacitance at a current density of 1 A / g was 520 F / g. After 1000 bending cycles, the capacitance retention was 94%.

[0037] The driving performance of the flexible actuation device obtained in this embodiment was tested. Under ±1.5V square wave voltage driving, the tip displacement amplitude was 15mm at a frequency of 0.1Hz; the tip displacement amplitude could maintain 40% of the tip displacement amplitude at a frequency of 10Hz.

[0038] Example 3 according to Figures 1-2 As shown, this embodiment provides a nanolayered MXene ion-crosslinked composite electrode and its flexible actuation device, the preparation method of which is as follows: Step 1: Add 1.5g of lithium fluoride to 15mL of 9mol / L hydrochloric acid solution and stir until the lithium fluoride is completely dissolved to obtain an etching solution. Then, add 1.5g of Ti3AlC2MAX phase powder to the etching solution and stir the reaction at 40℃ for 36 hours to obtain the reaction product. Next, wash the reaction product with deionized water until the pH value is 6.5, and then centrifuge to obtain Ti3C2T. x MXene precipitation, then Ti3C2T x MXene precipitate was dispersed in deionized water and subjected to ultrasonic exfoliation under inert gas protection for 2 hours. The supernatant dispersion was collected by centrifugation to obtain Ti3C2T. x MXene nanosheet dispersion.

[0039] Step 2: To Ti3C2T x Pyrrole monomer was added to the MXene nanosheet dispersion, and the pyrrole monomer reacted with Ti3C2T x The MXene nanosheets were mixed at a mass ratio of 0.6:1 and stirred at 3°C ​​for 45 minutes to obtain a mixed dispersion. Then, a 0.3 mol / L ammonium persulfate aqueous solution was added dropwise to this mixed dispersion. The molar ratio of ammonium persulfate to pyrrole monomer was 1.25:1. The reaction was carried out at 3°C ​​for 9 hours to allow the pyrrole monomer to react in Ti3C2T. x MXene nanosheets are polymerized in situ between layers to form polypyrrole, thus obtaining an MXene-polypyrrole composite dispersion.

[0040] Step 3: Add a 0.125 mol / L FeCl3 aqueous solution to the MXene-polypyrrole composite dispersion. The volume ratio of the FeCl3 aqueous solution to the MXene-polypyrrole composite dispersion is 1:12.5. Stir at room temperature for 3 hours to obtain the cross-linked composite dispersion.

[0041] Step 4: The cross-linked composite dispersion was deposited onto the surface of a polyvinylidene fluoride (PVDF) filter membrane with a pore size of 0.335 μm using vacuum filtration. The membrane was then dried under vacuum at 50°C for 18 hours. The dried composite film was then peeled off the filter membrane surface to obtain a nanolayered MXene ion-crosslinked composite electrode with a thickness of 27.5 μm. The nanolayered MXene ion-crosslinked composite electrode was then cut into a first electrode layer and a second electrode layer.

[0042] Step 5: Mix polyvinyl alcohol, deionized water, and phosphoric acid at a mass ratio of 1:10:1 and stir at 90°C for 3 hours to obtain a gel polymer electrolyte. Then, coat the gel polymer electrolyte onto the surface of the first electrode layer, and then cover the gel polymer electrolyte surface with the second electrode layer, creating a 6mm long misalignment region between the first and second electrode layers. This misalignment region is used to connect to an external driving power supply, while simultaneously filling the space between the first and second electrode layers with a gel polymer electrolyte layer thickness of 50μm. Afterward, allow it to cure at room temperature for 18 hours to obtain a flexible actuator.

[0043] Both the first and second electrode layers are rectangular sheet structures, with a sheet width of 6 mm and a sheet length of 25 mm. The thickness ratio of the first electrode layer to the second electrode layer is 1:1. The two ends of the first and second electrode layers are aligned in the width direction, and their first ends are flush in the length direction.

[0044] X-ray diffraction tests were performed on the nanolayered MXene ion-crosslinked composite electrode obtained in this embodiment, under the same test conditions as in Example 1. The interlayer distance was calculated to be 1.5 nm.

[0045] The electrochemical performance of the nanolayered MXene ion-crosslinked composite electrode obtained in this embodiment was tested, and the specific capacitance at a current density of 1 A / g was 450 F / g. After 1000 bending cycles, the capacitance retention was 89.5%.

[0046] The driving performance of the flexible actuator obtained in this embodiment was tested. Under ±1.5V square wave voltage driving, the tip displacement amplitude was 11.5mm at a frequency of 0.1Hz; the tip displacement amplitude could maintain 30% of the tip displacement amplitude at a frequency of 10Hz.

[0047] Comparative Example 1 This comparative example provides a nanolayered MXene-PPy composite electrode and its flexible actuation device. The only difference between this example and Example 3 is that no metal ion crosslinking agent solution is added in step 3; that is, the MXene-PPy composite dispersion obtained in step 2 directly enters step 4 for vacuum filtration and molding. The remaining parameters and operating steps are the same as in Example 3.

[0048] The nanolayered MXene-PPy composite electrode obtained in this comparative example was subjected to XRD testing under the same conditions as in Example 1. The interlayer distance was calculated to be 1.0 nm.

[0049] The electrochemical performance of the nanolayered MXene-PPy composite electrode obtained in this comparative example was tested, and the specific capacitance at a current density of 1 A / g was 310 F / g. After 1000 bending cycles, the capacitance retention was 72%.

[0050] The driving performance of the flexible actuator obtained in this comparative example was tested. Under ±1.5V square wave voltage driving, the tip displacement amplitude was 6.5mm at a frequency of 0.1Hz; the tip displacement amplitude at a frequency of 10Hz could maintain 18% of the tip displacement amplitude at a frequency of 0.1Hz.

[0051] The test results of Examples 1 to 3 and Comparative Example 1 are summarized in Table 1 below: Table 1 A comparison between Comparative Example 1 and Example 3 shows that: without the addition of a metal ion crosslinking agent, the interlayer distance of the MXene-PPy composite electrode is only 1.0 nm, lower than the 1.2 nm to 1.8 nm range specified in this invention; the specific capacitance is 310 F / g, lower than the 380 F / g to 520 F / g range of this invention's examples; the capacitance retention rate after 1000 bending cycles is only 72%, significantly lower than the 85% to 94% range of this invention's examples; the tip displacement amplitude at 0.1 Hz is 6.5 mm, lower than the 8 mm to 15 mm range of this invention's examples; and the attenuation ratio at 10 Hz is only 18%, lower than the 20% to 40% range of this invention's examples. These comparative results demonstrate that this invention, by adding a metal ion crosslinking agent to construct a coordination crosslinking network, can effectively increase the interlayer distance, improve the specific capacitance, enhance cycle stability, and improve low-frequency driving deformation capability.

[0052] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the present invention without departing from its framework and scope of application, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.

Claims

1. A nanolayered MXene ion-crosslinked composite electrode, characterized in that: The nanolayered MXene ion-crosslinked composite electrode contains Ti3C2T x MXene nanosheets, polypyrrole, and metal ion crosslinking agents, in a multilayer structure of Ti3C2T x MXene nanosheets are stacked to form a layered framework structure, wherein adjacent Ti3C2T nanosheets are in the layered framework structure. x The interlayer spacing between MXene nanosheets is 1.2 nm to 1.8 nm, and the polypyrrole is in situ filled in the interlayer space of the MXene nanosheets. The metal ion crosslinking agent and Ti3C2T x The oxygen-containing functional groups on the surface of MXene nanosheets form coordination bonds, and the nanolayered MXene ion-crosslinked composite electrode has a thin film structure with an electrode thickness.

2. The nanolayered MXene ion-crosslinked composite electrode according to claim 1, characterized in that: The metal ion crosslinking agent is selected from Fe. 3+ Ca 2+ Or Al 3+ One of them, the Ti3C2T x The mass ratio of MXene nanosheets to polypyrrole is 1:0.2 to 1:1, and the electrode thickness is 5 μm to 50 μm.

3. The nanolayered MXene ion-crosslinked composite electrode according to claim 1, characterized in that: The nanolayered MXene ion-crosslinked composite electrode has a specific capacitance of 380 F / g to 520 F / g at a current density of 1 A / g, and retains 85% to 94% of its capacitance after 1000 bending cycles.

4. A flexible actuator constructed using a nanolayered MXene ion-crosslinked composite electrode as described in claims 1 to 3, characterized in that: The flexible actuation device includes a first electrode layer, an electrolyte layer, and a second electrode layer stacked sequentially. Both the first and second electrode layers are nanolayered MXene ion-crosslinked composite electrodes. The electrolyte layer is a gel polymer electrolyte, which fills the space between the first and second electrode layers. Both the first and second electrode layers are rectangular sheet structures with sheet width and sheet length. The first electrode layer has a first electrode layer thickness, and the second electrode layer has a second electrode layer thickness. The first and second electrode layers form a misaligned region at their second ends in the length direction, and the misaligned region has a misaligned region length.

5. The flexible actuation device of the nanolayered MXene ion-crosslinked composite electrode according to claim 4, characterized in that: The gel polymer electrolyte is composed of polyvinyl alcohol, deionized water and phosphoric acid, and the mass ratio of polyvinyl alcohol, deionized water and phosphoric acid is 1:8:1 to 1:12:1; the thickness of the gel polymer electrolyte is 20μm to 80μm.

6. The flexible actuation device of the nanolayered MXene ion-crosslinked composite electrode according to claim 4, characterized in that: The sheet width is 2mm~10mm, the sheet length is 10mm~40mm, the ratio of the thickness of the first electrode layer to the thickness of the second electrode layer is 0.8:1~1.2:1, the first electrode layer and the second electrode layer are aligned at both ends in the width direction, the first electrode layer and the second electrode layer are flush at their first ends in the length direction, the misaligned area is 4mm~8mm long, and the misaligned area is used to connect to an external driving power supply.

7. The flexible actuation device of the nanolayered MXene ion-crosslinked composite electrode according to claim 4, characterized in that: The flexible actuator, driven by a ±1.5V square wave voltage, has a tip displacement amplitude of 8mm~15mm at a frequency of 0.1Hz, and at a frequency of 10Hz, the tip displacement amplitude can still maintain 20%~40% of the tip displacement amplitude at the 0.1Hz frequency.

8. A method for fabricating a flexible actuator, applied to the flexible actuator of the nanolayered MXene ion-crosslinked composite electrode as described in claim 4, characterized in that: Includes the following steps: Step 1: Add lithium fluoride to hydrochloric acid solution and stir until the lithium fluoride is completely dissolved to obtain an etching solution. Then, add Ti3AlC2MAX phase powder to the etching solution and stir the reaction at 35℃~45℃ for 24h~48h to obtain the reaction product. After that, wash the reaction product with deionized water until the pH value is 6~7, and then separate it by centrifugation to obtain Ti3C2T x MXene precipitation, then Ti3C2T x MXene precipitate was dispersed in deionized water and subjected to ultrasonic exfoliation under inert gas protection and light-protected conditions for 1-3 hours. The supernatant dispersion was collected by centrifugation to obtain Ti3C2T. x MXene nanosheet dispersion; Step 2: To Ti3C2T x Pyrrole monomer was added to an MXene nanosheet dispersion and stirred at 0℃~5℃ for 30min~60min to obtain a mixed dispersion. An oxidant solution was then added dropwise to the mixed dispersion, and the reaction was carried out at 0℃~5℃ for 6h~12h to allow the pyrrole monomer to react in Ti3C2T. x MXene nanosheets are polymerized in situ to form polypyrrole, resulting in an MXene-polypyrrole composite dispersion. Step 3: Add a metal ion crosslinking agent solution to the MXene-polypyrrole composite dispersion and stir at room temperature for 2-4 hours to obtain a crosslinked composite dispersion; Step 4: The cross-linked composite dispersion is deposited on the surface of the filter membrane by vacuum filtration and dried under vacuum for 12h~24h. The dried composite film is then peeled off from the surface of the filter membrane to obtain a nano-layered MXene ion cross-linked composite electrode. The nano-layered MXene ion cross-linked composite electrode is then cut into a first electrode layer and a second electrode layer. Step 5: Mix polyvinyl alcohol, deionized water and phosphoric acid in a mass ratio of 1:8:1 to 1:12:1, and stir at 85℃ to 95℃ for 2 to 4 hours to obtain a gel polymer electrolyte. Then, coat the gel polymer electrolyte onto the surface of the first electrode layer, and cover the surface of the gel polymer electrolyte with the second electrode layer, so that the gel polymer electrolyte fills the space between the first electrode layer and the second electrode layer. Allow it to stand and cure at room temperature for 12 to 24 hours to obtain the flexible actuator.

9. The method for fabricating a flexible actuation device according to claim 8, characterized in that: In step one, the concentration of the hydrochloric acid solution is 6 mol / L to 12 mol / L, the mass-to-volume ratio of lithium fluoride to hydrochloric acid solution is 1 g:10 mL to 1 g:20 mL, and the mass ratio of Ti3AlC2 MAX phase powder to lithium fluoride is 1:1 to 1:

2.

10. A method for fabricating a flexible actuation device according to claim 8, characterized in that: In step two, the pyrrole monomer reacts with the Ti3C2T x The mass ratio of MXene nanosheets is 0.2:1 to 1:1; the oxidant solution is an aqueous solution of ammonium persulfate, and the concentration of the aqueous solution of ammonium persulfate is 0.1 mol / L to 0.5 mol / L; the molar ratio of ammonium persulfate to pyrrole monomer is 1:1 to 1.5:1.